Proposta de avaliação e intervenção terapêutica por meio do jogo de tabuleiro “jogo da vida ocupacional” - PAIVA, Matheus de Almeida (2023)
The stroke results from the interruption of cerebral blood flow of diverse etiologies, which affects the supply of oxygen and nutrients to brain tissue and often culminates with physical, cognitive and occupational physics. One of the proposals of intervention of the occupational therapist to maintain the participation of people with stroke in their daily activities is favoring the balance between the maintenance of the motor / cognitive functions and the occupational performance, preserving the quality of life and increasing their sensation of well-being. Rehabilitation actions involve the use of a range of resources, standardized and / or developed in a specific way. In the process of rehabilitation, games can be facilitators in the identification and analysis of commitments and, on the other hand, can provide moments of pleasure, guaranteeing continuity to the occupational routine. Results found in the literature show that games have positive implications for improving self-perception, for favoring self esteem and for promoting social interaction and well-being. Based on the information presented on the motor and cognitive alterations resulting from the stroke and the potential contributions of the board games like strategies of occupational therapeutic intervention, this work aims to develop and propose a playful resource for evaluation and occupational therapeutical rehabilitation of post- stroke. It consists of a documentary study with a qualitative, descriptive and technological approach, in which a prototype board game, the "Occupational Life Game", is proposed for occupational therapists in a playful script, together with patients with neurology sequels coming from stroke, based on the degree of independence and autonomy they present to carry out selected daily activities. It is believed that this practical and low-cost resource extends the possibilities of intervention in Occupational Therapy, taking into account the Brazilian context in which high-cost electronic games do not routinely make up the resources within the public health units. In addition, it is possible this game possibility for the patient to extend their performance potential in daily occupations, contributing positively to their health and quality of life.